Assessing the relationship between brand message and guests’ choice in the Sarova hotel chain in Nairobi - Zipporah, Mwalimu; Macharia, Stephen; Kibe, Judy (Hotel and Tourism Management, 2019)
Hotels and restaurants in Kenya aim to distinguish their brand image and differentiate their product or service from competitors by implementing particular brand approaches. The effectiveness of hotel branding among the Sarova hotels in Kenya is key to competiveness of the hotel business according to the previous findings which announced that the Sarova Hotel had vibrant clientele from both local and international markets. Effective branding has persisted during the years and still attracts visitors. The objective of the study was to assess the relationship between brand message and guests’ choice in the Sarova hotel chain in Nairobi. The target population were the guests residing at the Sarova group of hotels in Nairobi for one week on leisure vacation. Out of 380 guests living in the hotels, the sample size was 191 guests. Descriptive and inferential statistics were used to analyze the data. Findings reveal that a successful brand messaging strategy for the Sarova hotel chain in Nairobi perceives the design of a coherent communication strategy in the process of destination brand management as one of critical forces of its competitiveness.